Teacher Education in the Time of COVID-19: Creating Digital Networks as University-School-Family Partnerships - Tracey S Hodges; Cailin Kerch; Melisa (Lisa) Fowler (Middle Grades Review, 2020)
As COVID-19 has suddenly transformed the landscape of learning in the United States, teachers are doing what they do best: figuring out how to effectively respond to support their students on their own. However, by creating digital networks that include university-school-family partnerships, the reach of teachers and teacher educators can increase. Teacher educators can provide support, systems, and strategies to maneuver the additional stressors and challenges posed by teaching during COVID-19. In this essay, we discuss how university-school-family partnerships mitigate the impacts of trauma, augment digital learning, and provide support for a variety of instructional scenarios happening in homes. Our focus on middle grade learners provides promise for meeting the needs of diverse students while capitalizing on the resources and expertise of universities, schools, teachers, and families.
Keywords: Teacher Education; COVID-19; Teachers; Social Media; Trauma; Middle Grades